Olenid trilobites: The oldest known chemoautotrophic symbionts? - Fortey, Richard (National Academy of Sciences, 2000)
Late Cambrian to early Ordovician trilobites, the family Olenidae, were tolerant of oxygen-poor, sulfur-rich sea floor conditions, and a case is made that they were chemoautotrophic symbionts. Olenids were uniquely adapted to this habitat in the Lower Paleozoic, which was widespread in the Late Cambrian over Scandinavia. This life habit explains distinctive aspects of olenid morphology: wide thoraces and large numbers of thoracic segments, thin cuticle and, in some species, degenerate hypostome, and the occasional development of brood pouches. Geochemical and field evidence is consistent with this interpretation. Olenids occupied their specialized habitat for 60 million years until their extinction at the end of the Ordovician.